Stories from a Geisha: Den stygge Andy - Hovda, Remi Johansen (Nordic Journal of Art & Research, 2015)
This article describes the development of the Stories from a Geisha. The work contains five different drag shows I a performative series with one thematic entirety. The thematic are brought from the cross fitting tradition in the Canadian army during the last world war. This article takes up the first show in the series, “The ugly Andy”, and discuss the work as a renewal of the drag genre. Verbal story telling and drag show are combined in Stories for a Geisha that stands as a new genre: StoryDrag. The whole show, “The ugly Andy” are available online (Art of Cassie, 2015).